Performance-based design optimization of tall concrete framed structures subject to wind excitations - Huang, M.F.; Li, Qiang; Chan, C.M.; Lou, W.J.; Kwok, K.C.S.; Li, G. (Journal of wind engineering and industrial aerodynamics, 2015)
This paper presents an integrated computational design optimization method for the performance-based design of tall buildings subjected to various levels of wind excitation. A performance-based wind engineering design framework is proposed by defining various performance objectives associated with multiple levels of wind hazards. A nonlinear static pushover analysis is employed to predict the inelastic drift performance of tall buildings subject to very rare extreme wind events. The optimal performance-based design problem considering inelastic deformation is formulated and solved by the augmented optimality criteria method. The effectiveness and practicality of the optimal wind-resistant performance-based design technique are illustrated by a practical 40-story residential building.